THE ELECTRON MICROSCOPY OF THE HUMAN HAIR FOLLICLE : PART 2. THE HAIR CUTICLE - Birbeck, M. S. C. (The Rockefeller University Press, 1957)
1. During the early differentiation of the cuticle the cell membranes smooth out and the cells become closely attached over most of their surface. The change seems to be due to a layer of cement which forms between them. The plasma membranes also increase in density. 2. The decreased membrane activity of the cuticle cells may prevent a phagocytosis of the melanocyte processes and thus account for the non-pigmentation of the cuticle. 3. The flattening and imbrication of the cuticle may possibly be explained by a zipper-like spread of cell contacts. 4. Keratinisation of the cuticle occurs at a late stage in its development; the keratin formed is an amorphous type, similar to the γ-fraction of the cortex which is produced at a similar level. 5. Keratinisation is accompanied by the formation of complex intercellular layers similar to structures observed in the inner root sheath (see Part 3). 6. In the final stage of keratinisation the remaining cytoplasm condenses with the result that the cell is divided into a laminated structure with an outer keratinised layer and an inner layer, which is insoluble in keratinolytic solvents.